Effectiveness and Safety of Rivaroxaban 15 or 20 mg Versus Vitamin K Antagonists in Nonvalvular Atrial Fibrillation: A Population-Based New Users High-Dimensional Propensity Score Matched Cohorts Study. Issue 9 (September 2019) - Blin, Patrick; Fauchier, Laurent; Dureau-Pournin, Caroline; Sacher, Frédéric; Dallongeville, Jean; Bernard, Marie-Agnès; Lassalle, Regis; Droz-Perroteau, Cécile; Moore, Nicholas
Abstract : Background and Purpose—: We compared the 1-year safety and effectiveness of rivaroxaban 15 mg (R15) or rivaroxaban 20 mg (R20) to vitamin K antagonists (VKAs) in patients with nonvalvular atrial fibrillation. Methods—: New user cohort study of patients dispensed R15 or R20 versus VKA in 2013 or 2014 for nonvalvular atrial fibrillation, followed 1 year in the French Système National des Données de Santé (66 million people). R15 and R20 users were matched 1:1 with VKA users on sex, age, date of first drug dispensing, and high-dimensional propensity score. Hazard ratios (95% CIs) for stroke and systemic embolism, major bleeding, and death were computed using Cox proportional hazards or models by Fine and Gray during exposure. Results—: In 31 171 matched R20 and VKA, mean age, 71; 62% men; 76% with CHA2 DS2 -VASc ≥2; 5% HAS-BLED >3 (hypertension, abnormal renal and liver function, stroke, bleeding, labile INR, elderly, drugs or alcohol); incidence rates for stroke and systemic embolism were 1.5% and 1.9% (hazard ratio, 0.79 [0.69–0.90]); major bleeding, 1.5% and 2.2% (0.67 [0.59–0.77]); death, 3.9% and 5.8% (0.67 [0.61–0.73]). In 23 314 matched R15 and VKA patients, mean age, 80; 47% men; 93% with CHA2 DS2 -VASc ≥2 and 9% with HAS-BLED >3; incidence rates of stroke and systemic embolism were 2.3% and 2.1% (1.05 [0.92–1.21]); major bleeding, 2.4% and 2.9% (0.84 [0.74–0.96]); death, 9.1% and 10.8% (0.85 [0.79–0.90]). Numbers needed to treat to observe one fewer death (NNT) were 46 for R15 and 61 for R20. Conclusions—: In real life in France over 2013 to 2015, R15 and R20 were at least as effective and safer than VKA. Clinical Trial Registration—: URL: http://www.encepp.eu . Unique identifier: EUPAS14567. Abstract : Supplemental Digital Content is available in the text.